Efeito da instrumentação periodontal na estrutura dentária afetada pela radiação ionizante: estudo in vitro - Cruz, Guilherme Gonçalves (2022)
Discuss the importance of non-surgical periodontal therapy in patients undergoing radiotherapy in the head and neck region. The effects that different scaling protocols have on the morphology and roughness of the substrate affected by ionizing radiation. One hundred and thirty extracted bovine incisors were randomly divided into two group (n=65): non-irradiated (NIR) and irradiated (IR). They were randomly subdivided according to the type of protocol of intervention: NIT: no instrumentation; NIT/PP: only prophylaxis with a fine prophylactic paste using a rubber cup coupled with a low-speed rotation device under constant irrigation for 15 seconds; HS: scaling using hand instrumentation with 15 apical-coronal movements; HS/PP: Hand instrumentation followed by prophylaxis protocol; US: scaling using a ultrasonic instrumentation, with 15 apical-coronal cycles. US/PP: ultrasonic instrumentation followed by prophylaxis protocol. The root surface roughness was measured with a profilometer and the morphological features of the root surfaces were analyzed using SEM. The data obtained from profilometer for were analyzed using, two-way ANOVA followed Tuckey`s (α= 0,05). For SEM Kappa test was used for assessing the inter-observer and ordinal logistic regression was used to analyze the effect of each factor on the scores. For the protocols with PP, the Ra and Rz values after the types of instrumentation were lower regardless of radiotherapy. The US groups had the highest Ra and Rz values regardless of radiotherapy. For the Ra variation, the following values were found: For groups NIr (HS-0.31 0.05, US-1.51 0.23) presented the most pronounced values, the prophylaxis has effect only on protocol (US/PP-0.19 0.06) ; For Ir (HS-0.46 0.07, US-2.23 0.25) also presented the most pronounced values, when compared to the Nir group the values presented statistical differences, prophylaxis has effect in both protocols (HS/PP-0.13 0.04, US/PP-0.20 0.03,). The statistical differences between the values found for RZ followed the parameters of Ra. For SEM a moderate concordance among the evaluators was observed (overall Kappa = 0.443). The substrate did not affect the scores. On the other hand, for ordinal logistic regression, both manual and ultrasonic instrumentation resulted in higher scores than no instrumentation; and the prophylaxis reduced the scores. Both manual and ultrasonic instrumentation resulted in rougher root surface irradiated than non-radiated dentin. However, the prophylaxis procedure following the instrumentation significantly reduced the roughness of root surfaces instrumented with either hand curettes or ultrasonic scallers. Prophylaxis alone did not significantly change the surface roughness.